MITIGASI REGULATORY CAPTURE DEMUTUALISASI BEI MELALUI INDEPENDENT LISTING AUTHORITY BERBASIS KOMPARASI AUSTRALIAN SECURITIES EXCHANGE - A’an Ilham Ardiyansah; Sang Ayu Putu Rahayu (CV. Denasya Smart Publisher, 2026)
The demutualization of the Indonesia Stock Exchange (IDX) has triggered a paradigm shift, transforming the exchange from a non-profit organization into a profit-oriented corporate entity. However, this transformation carries a latent risk of regulatory capture, where the exchange's supervisory functions are vulnerable to being co-opted by commercial interests in pursuit of listing fees. This article analyzes the failure of the current Self-Regulatory Organization (SRO) structure in mitigating institutional conflicts of interest, as evidenced by the declining trend in issuers' fundamental quality amidst aggressive IPO growth. Utilizing normative legal research and a comparative approach with the Australian Securities Exchange (ASX), this study finds that separating supervisory functions through an independent authority is an absolute prerequisite for market integrity. This article reconstructs the urgency of establishing an Independent Listing Authority (ILA) in Indonesia as a juridical firewall. This solution aims to sever the regulator's financial dependence on issuers, ensuring that listing decisions are based entirely on legal compliance and investor protection rather than the exchange's financial performance targets.